A real‐time interactive rendering method for 360° tabletop integral imaging 3D display. Issue 9 (29th April 2021) - Ma, Xiao‐Ming; Xing, Yan; Zheng, Jia‐Chen; Li, Xiao‐Wei; Wang, Qiong‐Hua
Abstract: In this paper, a rendering method for interactive tabletop integral imaging 3D display is proposed to present interactive 3D graphics to users 360° around the display in real‐time. By transforming the viewpoint plane and the elemental image array (EIA) plane with a parallel backward ray‐tracing technique according to the recognized gestures, a high‐efficient rendering for interactive 3D contents can be achieved, thus, the 3D graphics can be manipulated to be displayed on the tabletop in real‐time. Compared with the previous methods that all viewpoint images should be generated first, the proposed method can generate the interactive EIAs that contain all viewpoint information directly, which makes the interactive rendering more efficient. A gesture‐based interactive tabletop integral imaging 3D display prototype is built using an 8‐K (7680 × 4320) pixel resolution LCD. Experimental results show that the proposed interactive rendering method can achieve a short response time of less than 40 ms and high recognition accuracy of over 95% for different spatial hand gestures. Abstract : An interactive rendering method is proposed to present interactive 3D graphics to users around the tabletop integral imaging 3D display in real‐time. Compared with the previous methods that all viewpoint images should be generated first, the proposed method can generate the interactive EIAs that contain all viewpoint information directly, which makes the interactive rendering more efficient.